Tinjauan Ekonomi Syariah Terhadap Praktik Jual Beli Borongan Ikan Bandeng: Studi Kasus di Desa kalanganyar kecamatan Sedati Kabupaten Sidoarjo - Imam Mawardi (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
In this study, the system of buying and selling milkfish in bulk in ponds is still carried out by the people of Kalanganyar Village, Sedati District, Sidoarjo Regency until now. Fish buying and selling transactions with the wholesale system can be said to be gharar transactions or there is an element of ambiguity in the form and quantity of goods. Because of that, buying and selling uses a system of guessing the quality and quantity of goods before knowing the actual quality and quantity of goods. To find out more about how Islamic economic law deals with buying and selling milkfish with a wholesale system that is still in the pond. So a study is needed that discusses in depth the details of the study of sharia economic law in this case. In this study the authors used a qualitative descriptive method and in the study the researchers obtained data that supported this research by means of observation and interviews as well as documentation. The results of the observations and interviews were then developed by the author to find a result or a way out of this case. In this study, it can be concluded that the practice of buying and selling milkfish using a wholesale system in fish ponds contains elements of gharar (obscurity), because the quality and quantity of goods is not visible before making a transaction. So from this study came a conclusion that buying and selling is not valid according to the view of Islamic economics.